2017
DOI: 10.1016/j.jhep.2017.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base disorders in liver disease

Abstract: Alongside the kidneys and lungs, the liver has been recognised as an important regulator of acid-base homeostasis. While respiratory alkalosis is the most common acid-base disorder in chronic liver disease, various complex metabolic acid-base disorders may occur with liver dysfunction. While the standard variables of acid-base equilibrium, such as pH and overall base excess, often fail to unmask the underlying cause of acid-base disorders, the physical-chemical acid-base model provides a more in-depth pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 119 publications
1
82
0
4
Order By: Relevance
“…Traditionally, lactate has been deemed as a marker for tissue hypoxia, as lactate is overproduced and underutilized under these conditions due to impaired mitochondrial oxidation . Yet, the liver is responsible for up to 70% of whole‐body lactate clearance . Accordingly, especially acute hepatic impairment is associated with increased lactate levels .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, lactate has been deemed as a marker for tissue hypoxia, as lactate is overproduced and underutilized under these conditions due to impaired mitochondrial oxidation . Yet, the liver is responsible for up to 70% of whole‐body lactate clearance . Accordingly, especially acute hepatic impairment is associated with increased lactate levels .…”
Section: Discussionmentioning
confidence: 99%
“…(38) Yet, the liver is responsible for up to 70% of whole-body lactate clearance. (24,39) Accordingly, especially acute hepatic impairment is associated with increased lactate levels. (40) Additionally, in patients with fulminant hepatic failure and in ICU patients with cirrhosis, increased lactate was associated with poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, these patients had a better hepatic function compared to diabetic patients not treated with metformin. The low number of HCC patients receiving metformin can be explained by the fact that metformin use was thought to be associated with an increased incidence of lactic acidosis in patients with impaired liver function . However, a recent study in patients with mainly compensated cirrhosis showed that metformin treatment was not only safe but also improved survival in patients with diabetes and non‐alcoholic steatohepatitis (NASH)‐associated cirrhosis …”
Section: Discussionmentioning
confidence: 99%
“…The low number of HCC patients receiving metformin can be explained by the fact that metformin use was thought to be associated with an increased incidence of lactic acidosis in patients with impaired liver function. 38 However, a recent study in patients with mainly compensated cirrhosis showed that metformin treatment was not only safe but also Additionally, there is increasing evidence that treatment with metformin decreases the risk of various cancers including HCC. A pivotal, population-based cohort study including 10 309 patients with T2DM observed a significantly decreased cancer-related mortality for metformin compared to sulphonylurea and insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Отже, це є наслідком порушення білок-синтетичної функції печінки. Отримані дані збігаються з результатами клінічних досліджень обстежень, які додатково до печінкової дисфункції виявили порушення кислот-но-лужної рівноваги у хворих з ЦП [22]. Обмаль да-них наявна в літературі стосовно можливостей реви-користання АР при лікуванні ЦП -йдеться лише про ефективність реінфузії концентрата АР у пацієнтів з портальною гіпертензією [23].…”
Section: таблицяunclassified